Japan and the shaping of post-Vietnam War Southeast Asia Japanese diplomacy and the Cambodian conflict, 1978-1993 - Pressello, Andrea (Politics in Asia, 2018)
"The Vietnamese invasion of Cambodia in 1978 and the consequent outbreak of the Cambodian conflict brought Southeast Asia into instability and deteriorated relations between Vietnam and the subsequently established Vietnam-backed government in Cambodia on the one hand and the ASEAN countries on the other. As a result of the conflict, the Soviet Union established a foothold in Southeast Asia and China, through its support to the anti-Vietnam Cambodian resistance, improved relations with Southeast Asian countries such as Thailand. Japan's Fukuda Doctrine--its declared priorities of promoting cooperative and friendly relations with and among Southeast Asian countries to increase their stability--became increasingly at odds with its role as a member of the Free World in the broader Cold War confrontation. Tokyo had to steer a path between Washington's hardline policy of isolating Hanoi and its own desire to prevent regional destabilization. Against this background, this book addresses the following questions: how did Japan respond to the challenges to the post-Vietnam War Southeast Asian order that Tokyo had envisioned in the Fukuda Doctrine? What was the impact of the Japanese response on the stabilization and shaping of Southeast Asia and on Japan's role in the region? It argues that Japan's contribution was more active than has widely been recognized"-